Autores de violência sexual contra crianças e adolescentes: um estudo a partir da teoria sócio-histórica - Esber, Karen Michel (2008)
The main aim of this research is to examine the subjectivity of three sexual offenders against children and adolescents, who are imprisoned in a state prison (Agência Goiana do Sistema Prisional), based on Vygotsky´s socio-historical theory. Thus, the method of historical and dialectical materialism and the qualitative research approach were base structures for the adopted perspective. For the development of the research, three distinct methodological procedures were adopted: first, a literature research was conducted in Portal CAPES, from 2000 to 2006, in order to draw a brief overview of the international literature on the subject. In addition, theses, dissertations, books and articles produced by the national literature, also in the same period were reported. The second procedure consisted of a research on the subject´s files, held in the prision´s archives. In the third procedure, it was made an analysis of fifty one psychotherapy sessions with the three subjects, which was only possible though the actions of Projeto Invertendo a Rota (IDF/UCG) a project against child exploitation. Two meaning cores have emerged from the sessions: the suffered violence and the perpetrated violence. The analysis of these reports reveals that the three subjects were victims of sexual violence in their childhoods; in two of them, there was a certain difficulty in verbalizing the feelings related to the sexual violence they suffered, the three of them revealed fully awareness of the negative consequences of the violence they perpetrated, despite the attempts by two of them to minimize its negative effects on the victims; all of them confirmed having experienced feelings regarding the violence they perpetrated. In an attempt to list the reasons for practicing sexual violence, among other, all of them linked it to the experience of sexual violence suffered in childhood; for two of them, the meanings given to children show an understanding of them as sexual beings, benefited in some way by the sexual relation they practised; there is a consensus of the desire to no longer commit sexual violence. The meanings of the perpetrated sexual violence expressed by the three subjects are different: for one of them, it is linked to the need for revenge, to another one, it is conected to the sexual desire experienced towards adolescents; to the last one, it is linked the picture of the seductive child. Finally, this research enables to list some issues considered essential: the need for legal accountability for the violence they committed and the importance of the psychological treatment for the prevention of future recidivism.